Chinese Communication Studies: Three Paths Converging. (30th January 2017) - Jia, Wenshan
This contribution presents the possibilities for anthropological and neo-Marxist media within the hugely expanding sector of Chinese communication studies. China has sourced mostly from the American positivist tradition but is increasingly taking on board European critical thinking but it also needs to absorb some of the depth and diversity of indigenous scholarship existing in Chinese. Jia, Lu, and Heisey (2002 ) presented an influential meta-analysis of every example of communication studies in China at that time. The book chapter which talks about the rise of the discipline and scholarship of Chinese communication as an academic discipline (Jia et al., 2014 ) summarises some of Chinese language scholarship in Chinese and called for the creation of a humanistic tradition of Chinese and East Asia communication studies informed by indigenous perspectives and China's rich repertoire and vocabulary of concepts– face, guanxi or relations, goutong, harmony, and personhood etc. Concluding that there is a need for all parties to do research on journalism and communication/media in Asia, (particularly in China) from an anthropological perspective, this contribution argues that Asian scholars have a responsibility to create Asian approaches to communication and media studies. The effects of global neoliberalism is now being followed by a government response in China characterised in part by anti-corruption campaigns and a revival in Marxist approaches. A version of media studies that takes on board all the three elements would find fertile ground in the long run, supporting a more egalitarian and just China.